Isotropic Polymers: Density–Nematic Coupling in Isotropic Linear Polymers: Acoustic and Osmotic Birefringence (Adv. Theory Simul. 5/2019). Issue 5 (2nd May 2019) - Popadić, Aleksandar; Svenšek, Daniel; Podgornik, Rudolf; Praprotnik, Matej
Abstract : Elaborating on the tensorial conservation law for linear polymers and performing intensive Monte Carlo simulations, Aleksandar Popadić, Daniel Svenšek, Rudolf Podgornik, and Matej Praprotnik show in article number1900019 that a generic macrosopic coupling between density and orientational order occurs already in isotropic static polymer liquids, yielding osmotic optical birefringence induced by concentration gradients.